Penerapan Terapi Tiup Balon Untuk Mengurangi Sesak Nafas Pada Pasien Asma Melalui Aplikasi Teori Orem Di Rs Bhayangkara Bengkulu - Delvi Kembang Sari; Murwati Murwati (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Asthma is a chronic inflammatory disease of the airways characterised by recurrent symptoms of breathlessness, coughing, and wheezing, which can be exacerbated by various factors such as allergens, cold weather, and stress. One non-pharmacological intervention that can be used to reduce symptoms of breathlessness is balloon blowing therapy. This study aimed to evaluate the effectiveness of balloon blowing therapy through Orem's nursing theory approach in treating asthma patients at Bhayangkara Hospital in Bengkulu. The method used was a case study with a descriptive qualitative approach on two patients with ineffective breathing patterns. The intervention was carried out for three days using the balloon blowing technique. The results showed a decrease in respiratory rate, an increase in oxygen saturation, and a decrease in shortness of breath complaints after the intervention. Balloon blowing therapy proved to be effective as a supportive-educational effort in the Orem nursing system to increase patient independence in managing asthma symptoms. It can be concluded that this therapy is an effective complementary approach to reduce shortness of breath in asthma patients.